2018
DOI: 10.3390/jcm7120529
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia and Kidney Disease: More than Just an Incidental Finding?

Abstract: Peripheral blood eosinophilia (PBE), defined as 500 eosinophils or above per microliter (µL) blood, is a condition that is not uncommon but often neglected in the management of patients with chronic kidney disease (CKD), acute kidney injury (AKI), or patients on renal replacement therapy (RRT). The nature of PBE in the context of kidney diseases is predominantly secondary or reactive and has to be distinguished from primary eosinophilic disorders. Nonetheless, the finding of persistent PBE can be a useful clue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 262 publications
(347 reference statements)
0
20
0
1
Order By: Relevance
“…A prospective cohort study among US veterans demonstrated elevated peripheral blood eosinophil count in CKD cohort compared to cohort without CKD. Among patients with T2D, eosinophilia was associated with albumin excretion [72]. Eotaxin levels were elevated in the kidneys in Long-Evans rats on a high-fat diet.…”
Section: Discussionmentioning
confidence: 94%
“…A prospective cohort study among US veterans demonstrated elevated peripheral blood eosinophil count in CKD cohort compared to cohort without CKD. Among patients with T2D, eosinophilia was associated with albumin excretion [72]. Eotaxin levels were elevated in the kidneys in Long-Evans rats on a high-fat diet.…”
Section: Discussionmentioning
confidence: 94%
“…The peritoneal cavity is a major reservoir of eosinophils under homeostatic and inflammatory states [18] and where eosinophils become activated and cause effects on the peritoneum. Hypersensitivity and intraperitoneal inflammatory reactions induced by PD drive the activation of Th2 cells and other inflammatory cells [19,20], releasing cytokines including IL-5, granulocytemacrophage colony-stimulating factor (GM-CSF), and IL-3, which trigger eosinophil proliferation, activation, and chemotaxis to the peritoneum [21]. There are several possible changes to the peritoneum induced by activated eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…TSLP was associated with NF-κB signaling to elicit the inflammatory response. Other granule-derived peptides such as those produced by eosinophils ( 73 ), and granulysins that are secreted by cytotoxic T lymphocytes and NK cells ( 145 ), were reported in renal allograft rejection ( 76 , 77 ), and may also be linked with AKI and mortality ( 75 ).…”
Section: Pro-inflammatory Role Of Alarmins In Akimentioning
confidence: 99%